BODY HEIGHT AND ITS ESTIMATION UTILIZING ARM SPAN MEASUREMENTS IN FEMALE ADOLESCENTS FROM CENTRAL REGION IN MONTENEGRO - Marija Bubanja; Dobrislav Vujović; Gabrijela Doina Tanase; Rašid Hadžić; Rajko Milašinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
Anthropologists recognized the tallness of nations in the Dinaric Alps long time ago (Popovic et al, 2013). As the modern Montenegrins fall partly into the Dinaric racial classification (Bjelica et al., 2012), the purpose of this study was to examine the body height in Montenegrin female adolescents from central region as well as the relationship between arm span as an alternative to estimating the body height, which would vary from region to region in Montenegro. Method: Our investigation analyses 593 female adolescents from the central region in Montenegro. The anthropometric measurements were taken according to the protocol of the International Society for the Advancement of Kinanthropometry (ISAK). Means and standard deviations regarding the anthropometric measurements were obtained. A comparison of means of body heights and arm spans within this gender group were carried out using a t-test. The relationships between body height and arm span were determined using simple correlation coefficients and their 95% confidence interval. Then a linear regression analysis was performed to examine the extent to which the arm span can reliably predict body height. Results: The results displayed that female Central-Montenegrins are 169.24±11.61cm tall and have an arm span of 168.03±10.34cm. Discussion: Compared to other studies, the results of this study have shown that this gender made Central-Macedonians the tall population, taller than general female population in Montenegro (Bjelica et al., 2012). On the other hand, expectably, the arm span reliably predicts body height in this gender. However, the estimation equations which have been obtained in Central-Montenegrins are, different alike in general population, since arm span was shorter than the body heights (1.21±1.27 centimetres), much more than in general population (Bjelica et al., 2012). This confirms the necessity for developing separate height models for each region in Montenegro.